2017
DOI: 10.1128/jcm.02463-16
|View full text |Cite
|
Sign up to set email alerts
|

Point-Counterpoint: What Is the Optimal Approach for Detection of Clostridium difficile Infection?

Abstract: INTRODUCTION In 2010, we published an initial Point-Counterpoint on the laboratory diagnosis of Clostridium difficile infection (CDI). At that time, nucleic acid amplification tests (NAATs) were just becoming commercially available, and the idea of algorithmic approaches to CDI was being explored. Now, there are numerous NAATs in the marketplace, and based on recent proficiency test surveys, they have become the predominant method used for CDI diagnosis in the Uni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
78
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 118 publications
(80 citation statements)
references
References 68 publications
2
78
0
Order By: Relevance
“…Given the lack of a stand-alone C. difficile diagnostic that can sensitively and rapidly detect free toxins in stool, some experts recommend a multistep testing algorithm in which a nucleic acid amplification test (NAAT) or EIA GDH is performed in tandem with EIA toxin to rapidly identify toxin-positive and toxin Ϫ /NAAT ϩ patients to facilitate appropriate clinical decision-making (3,4). Proponents of toxin testing recommend that only toxin-positive patients be treated for CDI and toxin Ϫ /NAAT ϩ patients be evaluated clinically to determine if they have CDI or are colonized with C. difficile (3,4).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Given the lack of a stand-alone C. difficile diagnostic that can sensitively and rapidly detect free toxins in stool, some experts recommend a multistep testing algorithm in which a nucleic acid amplification test (NAAT) or EIA GDH is performed in tandem with EIA toxin to rapidly identify toxin-positive and toxin Ϫ /NAAT ϩ patients to facilitate appropriate clinical decision-making (3,4). Proponents of toxin testing recommend that only toxin-positive patients be treated for CDI and toxin Ϫ /NAAT ϩ patients be evaluated clinically to determine if they have CDI or are colonized with C. difficile (3,4).…”
Section: Discussionmentioning
confidence: 99%
“…Proponents of toxin testing recommend that only toxin-positive patients be treated for CDI and toxin Ϫ /NAAT ϩ patients be evaluated clinically to determine if they have CDI or are colonized with C. difficile (3,4). In this study, we showed that by defining a C T cutoff for GeneXpert C. difficile/Epi tcdB PCR, a sample-to-answer real-time PCR assay, we could sensitively predict 96.0% of toxin ϩ / PCR ϩ stool samples with an NPV of 97.1% and with a specificity of 78.0% using RMEIA toxin and CCNA as the reference method.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These categories are complicated by the association of many medications, including antimicrobials, with diarrhea, as well as overlapping symptoms between CDI and viral causes of hospital-acquired diarrhea and increased likelihood of C. difficile colonization in individuals with antibiotic and healthcare exposures [28]. There is intense debate around the use of antigen testing versus molecular for the diagnosis of CDI, which is beyond the scope of this review [29]. Suffice to say that diagnostic and ASP partnerships are necessary to reduce syndromic GI panel testing that detects colonization and subsequent unnecessary treatment.…”
Section: Gastrointestinal Tract Infection Syndromic Panelsmentioning
confidence: 99%